The partitioning of poleward energy transport response between the atmosphere and Ekman flux to prescribed surface forcing in a simplified GCM - Sarah M. Kang; Yechul Shin; Francis Codron (Geoscience Letters, 2018)
Abstract Recent studies have indicated that ocean circulation damps the atmospheric energy transport response to hemispherically differential energy perturbations, thereby muting the shifts of the Inter-Tropical Convergence Zone (ITCZ). Here, we focus on the potential role of Ekman heat transport in modulating this atmospheric response. An idealized representation of Ekman-driven heat transport (F E) is included in an aquaplanet slab ocean coupled to a gray radiation atmospheric model. We first alter the strength of F E in the control climate by tuning the gross stability of the Ekman layer S E. For a wide range of F E, the total poleward transport of energy remains nearly unchanged, but the ocean transports an increasing share for larger S E. The control climate is then perturbed by adding surface cooling in the Southern Hemisphere and warming in the Northern Hemisphere. The Ekman coupling damps the atmospheric energy transport response, as in previous coupled model experiments with full ocean dynamics. The ratio of the changes in Ekman to atmospheric energy transport is determined by the ratio of the gross stability in the Ekman layer to the atmosphere in the control climate, and is insensitive to the amplitude and location of forcing. We find that an unrealistically large S E is needed to reproduce the ratio of the changes in cross-equatorial oceanic to atmospheric energy transport in fully coupled models. The limited damping effect of Ekman transport highlights the need to examine the roles of deep circulation and subtropical gyres, as well as ocean heat uptake processes.